Fourfold alkoxy-substituted (2.2.2)paracyclophane-1,9,17-trienes-ROMP into PPVs with unusual topologies - Mäker, Dominic; Bunz, Uwe H. F. (Macromolecular rapid communications, 2014)
The synthesis of two 4,7,12,15-tetrakisalkoxy-substituted [2.2.2]-paracyclophane-1,9,17-trienes and their polymerization employing ring opening metathesis polymerization (ROMP) using Ru-carbenes (third-generation Grubbs catalyst) is reported. Phenylene ethynylene trimers are reduced via a Grignard reagent, followed by an intramolecular McMurry cyclization to give the cyclophenes. The cyclophenes are polymerized into soluble poly(para-phenylene vinylene)s (PPV), which are analyzed in solution by NMR, UV-vis, and fluorescence spectroscopy. They are spin coated into amorphous, fluorescent thin films, and investigated by optical spectroscopy and cyclic voltammetry.
Gesehen am 28.10.2020